Christ and culture: a global perspective - Daughrity, Dyron B. (Routledge, Taylor & Francis Group, 2025)
"Christianity has grown dramatically over the last few centuries and is now the largest religion in the world, embraced by more than 2.5 billion people from all over the globe. No longer just a European faith, Christianity is now border-less with heartlands in Brazil, the Congo, and the Philippines. Christ and Culture: A Global Perspective introduces students to how Christianity has been adopted by some of the world's cultures in surprising and fascinating ways. Case studies include: · Nairobi, Kenya · Lake Tana, Ethiopia · Bangalore, India · Stockholm, Sweden · Buenos Aires, Argentina · Jerusalem, Israel · Turin, Italy · Los Angeles, USA Within these chapters topics such as global Pentecostalism, Catholic-Protestant relations, Orthodoxy, reverse missions, secularisation, and urbanization are discussed. With allusions to H. Richard Niebhur's classic text (1951) on the topic throughout. With engaging case studies throughout, this book will be essential reading for students introduced to Christianity, Christianity and culture, and global Christianity for the first time"--